Formadores de Professores de Língua Inglesa: Uma experiência de colaboração e reflexâo - Eliane Carolina de Oliveira (2008)
This study was carried out with a group of 18 foreign language teacher educators (including myself as a research participant) from 11 different university contexts both from the public and the private sectors in the state of Goiás. The aim of the research was two-fold. First, it aimed at gathering teacher educators from different locations within the State, so that they could discuss themes concerning their work with pre-service and in-service education. Second, it sought to acquire an in-depth knowledge of the teacher educators identities, contexts and their practices with undergraduate students. In order to do that, a virtual group was created providing the space for interactions without geographical constraints. The studies in the theoretical background point out the lack of research concerning teacher educators on one hand (RICHARDSON, 1996; PIMENTA and ANASTASIOU, 2002; ALTET et al. 2003; MIZUKAMI, 2005) and the use of a more social and collaborative view of reflection by student teachers and teacher educators alike on the other (ZEICHNER and LISTON, 1990; PESSOA, 2002; HAWKINS and IRUJO, 2004; JORGE, 2005). In order to conduct this investigation, a qualitative research was undertaken and data were collected by means of autobiographies, interviews, questionnaires as well as the messages exchanged by the participants in the virtual interactions. The results show that teacher educators identity construction draws on several sources including their own language learning experiences at language learning institutions, at teacher training courses and their language education undergraduate courses at university. As an outcome, the conceptual orientations underlying the teacher educators practice resemble, both in practical and theoretical aspects, the models they experienced. The results also show that the process of undertaking a more collaborative reflective practice may be affected by each individuals personality traits.